Los relatos escépticos sobre la Transición española : origen y claves políticas e interpretativas - Gonzalo Pasamar (Les Cahiers de Framespa)
This article examines the sceptical interpretations of the Spanish transition to democracy from the years this change took place to the present. The analysis is focused upon their political roots, specific origins and relevant examples with the help of sources such as opinion articles, political essays, novels, and historical writings. The conclusion obtained is that these pessimist views have been subject to a range of narratives and political perspectives vividly developed during the last three decades in a context where political and cultural changes have strongly made their present felt.